Cerebrovascular plasticity: Processes that lead to changes in the architecture of brain microvessels. Issue 8 (August 2019) - Bogorad, Max I; DeStefano, Jackson G; Linville, Raleigh M; Wong, Andrew D; Searson, Peter C
The metabolic demands of the brain are met by oxygen and glucose, supplied by a complex hierarchical network of microvessels (arterioles, capillaries, and venules). Transient changes in neural activity are accommodated by local dilation of arterioles or capillaries to increase cerebral blood flow and hence nutrient availability. Transport and communication between the circulation and the brain is regulated by the brain microvascular endothelial cells that form the blood–brain barrier. Under homeostatic conditions, there is very little turnover in brain microvascular endothelial cells, and the cerebrovascular architecture is largely static. However, changes in the brain microenvironment, due to environmental factors, disease, or trauma, can result in additive or subtractive changes in cerebrovascular architecture. Additions occur by angiogenesis or vasculogenesis, whereas subtractions occur by vascular pruning, injury, or endothelial cell death. Here we review the various processes that lead to changes in the cerebrovascular architecture, including sustained changes in the brain microenvironment, development and aging, and injury, disease, and repair.